Association between Relative Risk Factor (RR) and ABO Blood Groups with Clinical Parameters in Patients with SARS-Cov-2: Hubungan antara Faktor Risiko Relatif (RR) dan Golongan Darah ABO dengan Parameter Klinis pada Pasien SARS-Cov-2 - Abdullah Fakhir Yousif; Abeer Ghassan Mahdi (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates the correlation between ABO blood groups and SARS-CoV-2 infection among 1,303 participants from Babylon, comprising 397 infected individuals and 906 healthy controls. It explores three primary axes: genetic inheritance of ABO blood groups in 200 families, distribution of these blood groups in the context of SARS-CoV-2 infection, and the relationship of these blood groups with various physiological indicators in infected, recovered, and healthy subjects. The findings reveal that the AB blood group is disproportionately associated with a higher infection rate (RR = 1.808), whereas the O group shows a lesser susceptibility (RR = 0.901). Additionally, physiological changes such as decreased lymphocytes, MCH, and MCHC, alongside increased WBC, CRP, Ferritin, D-dimer, and LDH levels were noted in infected individuals. This study underscores the potential of ABO blood groups as a factor in COVID-19 infection risk, suggesting a direction for future research into tailored medical responses based on genetic predispositions. Highlights: Blood Group Impact: AB group had higher COVID-19 infection rates; O group had lower. Physiological Indicators: Infected individuals showed significant changes in key blood parameters. Medical Strategy: Findings suggest potential for personalized medical approaches based on ABO blood groups. Keywords: SARS-Cov-2, ABO Blood Groups, Relative Risk Factor